2018
DOI: 10.3389/fpubh.2018.00124
|View full text |Cite
|
Sign up to set email alerts
|

Developing Workforce Capacity in Public Health Informatics: Core Competencies and Curriculum Design

Abstract: We describe a master’s level public health informatics (PHI) curriculum to support workforce development. Public health decision-making requires intensive information management to organize responses to health threats and develop effective health education and promotion. PHI competencies prepare the public health workforce to design and implement these information systems. The objective for a Master’s and Certificate in PHI is to prepare public health informaticians with the competencies to work collaborativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…Future studies should include questions more specific to PHI, for example, designing, implementing, and evaluating information systems; use of methods in capturing, storing, exchanging, and using data; and applying technologies and standards to enhance timeliness, completeness, and accuracy. Additional PHI-specific competencies have been suggested by Wholey and colleagues 19…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Future studies should include questions more specific to PHI, for example, designing, implementing, and evaluating information systems; use of methods in capturing, storing, exchanging, and using data; and applying technologies and standards to enhance timeliness, completeness, and accuracy. Additional PHI-specific competencies have been suggested by Wholey and colleagues 19…”
Section: Discussionmentioning
confidence: 97%
“…The PH WINS training needs assessment captured respondents' perceived skills and needs using 21 questions across 8 “strategic skill” domains 18. For the current analysis, we focused on questions addressing core public health competencies possessing the greatest overlap with PHI competencies 19. Selected training questions included the following: identifying appropriate sources of data and information to assess the health of a community; collecting valid data for use in decision making; participating in quality improvement processes for agency programs and services; and identifying evidence-based approaches to address public health issues.…”
Section: Methodsmentioning
confidence: 99%
“…There is an increased focus on public health information and knowledge management systems highlighting need for public health professionals skilled in designing and implementing these systems. Prior study has shown that four competency sets adequately represented in public health informatics curriculum including Leadership and System Thinking Skills, followed by Financial Planning and Management Skills, Community Dimensions of Practice Skills, and Policy Development/Program Planning Skills [33].…”
Section: Discussionmentioning
confidence: 99%
“…Informatics is recognised as a core competency for MPH students as defined by the Council on Education in Public Health. 5 More recently, the Council for State and Territorial Epidemiologists (CSTE) identified informatics as a top training priority to support achievement of public health department capacity needs. 6 There exist a variety of training options in public health informatics.…”
Section: Competencies and Training In Public Health Informaticsmentioning
confidence: 99%